PENGARUH LUAS LAHAN, PRODUKSI, DAN HARGA TERHADAP VOLUME EKSPOR KOPI INDONESIA - Dewi, Ni Wayan Dithania Kresta; Utama, Made Suyana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 9 (2022): VOL11NO 9, SEPTEMBER 2022 [3325-3700]DO - 10.24843/EEP.2022.v11.i09.p04, 2022)
Most of the coffee production in Indonesia is for export commodities and is the 4th coffee exporting country in the world. This can prove that coffee export commodities from Indonesia can compete with other coffee exporting countries in the world. The high export of coffee commodities from Indonesia has contributed greatly to the world as a supplier of coffee.This study aims to determine the effect of land area, production, and price simultaneously and partially on the volume of Indonesian coffee exports. The type of data used in this research is secondary data in the form of quantitative obtained from the directorate general of plantations and the Central Statistics Agency (BPS). This research was conducted in all provinces in Indonesia. The data analysis technique used in this study is multiple linear regression analysis. The results showed that land area, production, and price simultaneously affected the export volume of Indonesian coffee. Land area, production, and prices partially have a positive effect on the volume of Indonesian coffee exports. In accordance with these results, the importance of monitoring and socialization is to increase the area of ??coffee land as a medium for commodity in the production process, where this will have a maximum effect on increasing the volume of Indonesian coffee exports. Key words : land area, production, price, export, coffee.